What teachers need to know about language - Adger, Carolyn Temple; Snow, Catherine E.; Christian, Donna (Multilingual Matters, 2018)
This book shows what teachers need to know about language to work effectively with diverse students. It gives examples of the many aspects of teaching and learning in which language is a key, and it suggests how teacher education programs can help teachers gain the knowledge and skills they need to refine their practice.
Keywords: Linguistic minorities -- Education -- United States.; Children of minorities -- Education -- United States.; Teachers -- In-service training -- United States.; Language and education -- United States.; Minorités linguistiques -- Éducation -- États-Unis.; Enfants issus des minorités -- Éducation -- États-Unis.; Enseignants -- Formation en cours d'emploi -- États-Unis.; Educational strategies & policy.; Language teaching theory & methods.; Multicultural education.; Teaching skills & techniques.; EDUCATION -- Administration -- General.; EDUCATION -- Organizations & Institutions.; Children of minorities -- Education; Language and education; Linguistic minorities -- Education; Teachers -- In-service training; United States; EDUCATION / Bilingual Education